Mengimpor Kedelai: Perlukah Terus Dilanjutkan? (Pengaruh Liberalisasi Perdagangan terhadap Perkedelaian Indonesia) - Amaliyah, Ridha (Global and Policy Journal of International Relations, 2013)
ABSTRACTThis article explain the impact of Agreement on Agriculture (AoA) toward Indonesia’s food security, by evaluating imported soybean case. The concept of trade liberalization and food security can be used as theoretical frameworks. Based on AoA, all member countries should gradually reduced and eliminated any kind of protection, subsidy, and all non-tariff barriers. As the consequence, domestic market has to deals with liberal global market. Nevertheless, most of developed countries actually still protect their farmers, through provision of farming subsidy and market support. Unlike developed countries, Indonesia has no ability to significantly provide domestic support to its farmers. As one of strategic commodities, soybean has its political reasons and public policy to be protected. Ironically, even though many critics were delivered, Indonesian government had seen importing soybean as an endeavor to achieve national food security goal.Keywords: agreement on agriculture, imported soybeans, trade liberalization, food security.DOI:https://doi.org/10.33005/jgp.v1i01.2007